The Inter-Faith Commision (IFC): implications toward the issue of apostasy, Article 11 and Article 121 (1A) Federal Constitution / Muhammad Akram Abdul Aziz, Muhammad Hafizullah Ahmad and Effendy Zulkifly - Abdul Aziz, Muhammad Akram; Ahmad, Muhammad Hafizullah; Zulkifly, Effendy (2007)
This research was conducted for the purpose of gathering information with regards to the Inter-Faith Commission (IFC), a Commission proposed to be set up for the purpose of conducting inter-religious dialogues among various religions in Malaysia. Information that was gathered includes the important aspects of the Commission, which were the powers and functions of the IFC itself. Based on the gathered sources of information, this research managed to point out three of the affected areas if IFC is established in Malaysia; the issue of apostasy, Article 11 and also Article 121 (1A) Federal Constitution. Discussions with regards to the affected areas were made based on the views of the supporters of IFC as well as those who opposed its establishment. By applying the arguments from both sides with regards to IFC, several hypothetical implications have been identified that may or may not become reality if the Commission does exist. Again, the hypothetical implications were identified according to the affected areas which this research has identified. Lastly, conclusions on the implication of IFC have been made, which discuss whether it would bring positive or negative impacts on the areas that this research has discussed. Recommendations with regards to whether IFC should be established, as well as other relevant issues were made at the end of the research.